Do proton pump inhibitors affect the effectiveness of cyclin-dependent kinase 4/6 inhibitors in advanced HR positive, HER2 negative breast cancer? A meta-analysis - Moraes, Francisco Cezar Aquino de; Pereira, Caroline R. M.; Sano, Vitor Kendi Tsuchiya; Laia, Estella Aparecida De; Stecca, Carlos; Burbano, Rommel Mario Rodríguez (Frontiers in Pharmacology, 2024)
Background:The CDK 4/6 inhibitors, including palbociclib and ribociclib, are the standard first-line treatment for hormone receptor-positive (HR+) and human epidermal growth factor receptor 2-negative (HER2-) metastatic breast cancer. Proton pump inhibitors are one of the most globally prescribed types of medications as part of the treatment for gastroesophageal reflux and heartburn complaints. Medication interactions have been demonstrated, leading to a decrease in the effectiveness of chemotherapy drugs such as capecitabine and pazopanib. However, their role and interaction with targeted therapies such as CDK inhibitors are still poorly understood. Methods: We searched PubMed, Embase and Web of Science databases for studies that investigated the use of PPI with CDK 4/6 inhibitors versus CDK4/6 alone for advanced or metastatic breast cancer. We systematically searched for the currently available CDK inhibitors: palbociclib, ribociclib and abemaciclib. We computed hazard ratios (HRs), with 95% confidence intervals (CIs). Results: A total of 2737 patients with advanced breast cancer in 9 studies were included, with six studies described the status menopausal as 217 (7.9%) pre-menopause and 1851 (67.6%) post-menopause, for endocrine sensitivity only five studies described1489 (54.4%) patients were endocrine-sensitive and 498 (182%) endocrine-resistent, 910 (33.2%) patients used PPIs. The overall Progression-Free Survival was in favor of the PPI non-users (HR 2.0901; 95% CI 1.410-2.9498; p < 0.001). As well as the subgroup taking palbociclib, revealing statistical relevance for the PPI non-users (HR 2.2539; 95% CI 1.3213-3.8446; p = 0.003) and ribociclib subgroup with a slight decrease in hazard ratio (HR 1.74 95% CI 1.02-2.97; p=0.04; I²=40%). In the multivariate analysis, there was no statistical signifance with ECOG (HR 0.9081; 95% CI 0.4978-16566; p 0.753) and Age (HR 1.2772; 95% CI 0.8790-1.8559; p =0.199). Either, the univariate analysis did not show statistical significance. Conclusion: Women with HR+ and HER2- advanced metastatic breast undergoing treatment with targeted therapies, specifically CDK 4/6 inhibitors, should be monitored for the use of proton pump inhibitors. Therefore, the use of PPIs should be discussed, weighing the advantages and disadvantages for specific cases. It should be individualized based on the necessity in clinical practice for these cases.